2019
DOI: 10.1177/2325967118825066
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder and Elbow Range of Motion Can Be Maintained in Major League Baseball Pitchers Over the Course of the Season, Regardless of Pitching Workload

Abstract: Background:Studies examining the evolution of shoulder and elbow range of motion (ROM) in baseball pitchers over a single season have yielded inconsistent results.Purpose:To evaluate shoulder and elbow ROM in Major League Baseball (MLB) pitchers over a single season and to assess for correlations between these changes and measures of a pitcher’s workload.Study Design:Case-control study; Level of evidence, 3.Methods:Bilateral shoulder ROM (internal rotation [IR], external rotation [ER], and total range of motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Discrepancies between results of the current study and previous studies may be attributed to the different testing protocol positions. Shoulder ROM adaptations, increase in ER and increase/maintenance in IR, over the course of the season were comparable to the adaptations seen in previous studies [25,45,46]. Literature has shown that a side-to-side difference of 5 ° or more in TAM between the throwing and non-throwing arm may place athletes at increased risk of injury [20,22].…”
Section: Shouldersupporting
confidence: 80%
“…Discrepancies between results of the current study and previous studies may be attributed to the different testing protocol positions. Shoulder ROM adaptations, increase in ER and increase/maintenance in IR, over the course of the season were comparable to the adaptations seen in previous studies [25,45,46]. Literature has shown that a side-to-side difference of 5 ° or more in TAM between the throwing and non-throwing arm may place athletes at increased risk of injury [20,22].…”
Section: Shouldersupporting
confidence: 80%
“…Such programs included manual soft tissue release and stretching of the posterior rotator cuff, manual soft tissue release of anterior musculature (pectoralis minor/ major), and a thoracic ROM program. 21 Cross-body stretching was utilized in the players in this study as a treatment strategy to maintain acceptable shoulder IR and humeral adduction (see the Appendix, available in the online version of this article).…”
Section: Arm Care Protocolmentioning
confidence: 99%
“…2 A similar noted increase in HAdd ranging between 15.7° and 17.5° in professional baseball players from pre to post-intervention. 35,36 While Chan et al 35 did not provide an intervention, all players participated in posterior shoulder stretching drills which may have accounted for their observations. McGraw et al 36 provided a stretching and mobilization intervention, but only for athletes that exhibited a deficit in ER, IR, or HAdd in their throwing arm compared to their non-throwing arm.…”
Section: Discussionmentioning
confidence: 98%
“…35,36 While Chan et al 35 did not provide an intervention, all players participated in posterior shoulder stretching drills which may have accounted for their observations. McGraw et al 36 provided a stretching and mobilization intervention, but only for athletes that exhibited a deficit in ER, IR, or HAdd in their throwing arm compared to their non-throwing arm. The current intervention similarly included soft tissue mobilization of the posterior shoulder musculature with a lacrosse ball or Theragun (Therabody, Los Angeles, CA), as well as cross-body stretching, yet increases in Hadd were less than half that of previous literature.…”
Section: Discussionmentioning
confidence: 98%